MALAYSIAN INTERNET USER’S MOTIVATION AND CONCERNS FOR SHOPPING ONLINE - Mohd. Suki, Norazah bte (Malaysian Journal of Library and Information Science, 2001)
This study focuses on identifying the factors that motivate Malaysian Internet users’ browsing or purchasing behaviour through the Internet and the concerns, which affect online buying. A total of 579 randomly selected respondents from the states of Penang, Wilayah Persekutuan and Selangor, Malaysia answered the questionnaire and the data was analysed using factor analysis to identify the possible predictors. The findings indicate that seven motivating factors: accessibility (the most important factor), reliability, convenience, distribution, socialisation, searchability, and availability (the least important factor) accounted for 61.402% of total variance. Of the 38 statements posed to respondents, 33 statements were selected based on criteria of eigenvalues greater than or equal to 1.00, factor loading of 0.50 or higher. The results indicate all of these factors were appropriate for further analysis and the model possessed convergent validity. There were eight “concern” factors extracted with cumulative percentage of 62.405% of variance. The pertaining factors were privacy (the most important factor), reluctance to change, quality of products and services, security of payment modes, speed of connection, the reluctance to change attitude, the difficulty in trusting vendors and non-disclosure of complete product information (the least important factor). It is concluded that electronic transactions should provide a secure, reliable and trusted environment in order to attract and maintain existing users of the Internet to shop online.